Some Peculiarities of Functioning of the Concepts «Peace» and «War» in the Linguistic Consciousness of 9–13 Year-old Children with the Accounting of Gender Parameter - Галунова, Наталія Миколаївна; Васянович, Євгенія Андріївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The paper is devoted to an actual for modern Ukrainian linguistics problem of studying of the concepts of «peace» and «war» in the language picture of the world, particularly of middle school-aged children, taking into account the gender parameter. The materials for the research are associative reactions that were obtained in the chain associative experiment which was held with 9–13 year children. The analysis of the experimental results showed the impact of gender stereotypes on the semantic content of the concept of «peace» and «war».